Transverse nonlinear vibration of the eccentric rotor in a 12/8 switched reluctance motor. Issue 8 (8th April 2020) - Wang, Feng; Wu, Zhiqiang; Li, Yajie; Wang, Yuancen
Abstract : Purpose: To investigate transverse vibration of the eccentric rotor in a 12/8 poles switched reluctance motor (SRM), a transverse analytical vibration model is built by finite element method (FEM) under the interaction of radial magnetic resultant and vibration displacement. External forces, including radial magnetic resultant and centrifugal force, are also derived in detail, according to the variation of airgap and current and other intermediate parameters with rotation angle. Design/methodology/approach: The transverse vibration response of the eccentric rotor including radial magnetic resultant and vibration displacement is solved by Newmark- β method, after inputting the currents of three phase windings under angle position control strategy. The basic characteristics of radial magnetic resultant and vibration displacement are reflected in time and frequency domain. Findings: The magnetic resultant vector of the eccentric rotor presents multi-petals star geometric shape. The frequency distribution of magnetic resultant relates to rotation speed, current waveform and the least common multiple of the stator and rotor teeth. However, the frequency distribution of the vibration displacement also relates closely to the first-order critical whirl speed of the rotor. When the rotor is running at certain speeds, it will display superharmonic resonance and show abundant displacement locus. Originality/value: By using this analytical model and solving process proposed in this paper, the nonlinear coupled vibration response of the eccentric rotor in SRM can be analyzed and discussed rapidly; only the stator's winding currents obtained by experiment or electromagnetic simulation is needed as input.